FAKTOR – FAKTOR YANG MEMENGARUHI HARGA SAHAM PERUSAHAAN PERKEBUNAN DI BURSA EFEK INDONESIA TAHUN 2008-2016 - Ifan Rizky Kurniyanto; Bayu Krisnamurthi (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2018)
Capital markets allows the plantation companies to obtain long-term sources of funding for business expansion. To Invest in the stock market investors require careful consideration of accurate information to determine the relationship of variables that cause the fluctuation of the company's stock price to be purchased. Knowing the influence of these variables, investors can choose a strategy to determine the right company as a place to invest. The purpose of this study is to analyze technically and fundamentally shares of plantation companies that have been listed on the BEI in period of 2008-2016. Research method using panel data and Ipot Ultima. The results of this study showed that through fundamental analysis it is known that ROA, Inflation, Exchange Rate, and BI Rate and AR1 have a significant influence (Pvalue <0.05) on stock prices while CR, DER, TOTA, PER, NPM have no significant effect on stock price plantation. Through technical analysis it is known that the movement of plantation company in MA 3025 is sideway.